Statistiek en inferensie* - Venter, J. H. (Koers, 1968)
Een van die mees vooraanstaande wiskundiges wat hierdie eeu geleef het, Von Neumann,6 het een keer ’n voordrag m et die volgende opm erking ingelei: „A discussion of the nature of intellectual work is a diffi cult task in any field, even in fields which are not so far removed from the central area of our common hum an intellectual effort as mathematics still is. A discussion of the nature of intellectual effort is difficult per se — at any rate, more difficult than the mere exercise of that particular effort. It is harder to understand the mechanism of an airplane, and the theories of the forces which lift and which propel it, than merely to ride in it, to be elevated and transported by it — or even to steer it. It is exceptional that one should be able to acquire the understanding of a process without having previously acquired a deep familiarity with running it, with using it, before one has assimilated it in an instinctive and empirical way.